2017
DOI: 10.48550/arxiv.1708.09787
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Leray's fundamental work on the Navier-Stokes equations: a modern review of "Sur le mouvement d'un liquide visqueux emplissant l'espace"

Abstract: This article offers a modern perspective which exposes the many contributions of Leray in his celebrated work on the Navier-Stokes equations from 1934. Although the importance of his work is widely acknowledged, the precise contents of his paper are perhaps less well known. The purpose of this article is to fill this gap. We follow Leray's results in detail: we prove local existence of strong solutions starting from divergence-free initial data that is either smooth, or belongs to H 1 , L 2 ∩ L p (with p ∈ (3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…This programme was originally carried out by Leray, see [Ler34], and now constitutes an important result in the wider programme to establish existence and uniqueness of strong solutions to the Navier-Stokes equations. A review of Leray's work in English can be found in [Far17] and the preprint [OP17]. A fuller survey of results concerning the Navier-Stokes equations can be found in [Ser14a] (available as [Ser14b]).…”
Section: Any Bounded Setmentioning
confidence: 99%
“…This programme was originally carried out by Leray, see [Ler34], and now constitutes an important result in the wider programme to establish existence and uniqueness of strong solutions to the Navier-Stokes equations. A review of Leray's work in English can be found in [Far17] and the preprint [OP17]. A fuller survey of results concerning the Navier-Stokes equations can be found in [Ser14a] (available as [Ser14b]).…”
Section: Any Bounded Setmentioning
confidence: 99%
“…Leray [7] provides an outline of how to prove (1.1), using what is now known as the mild formulation of the Navier-Stokes equations. More recent proofs of (1.1) using the mild formulation include [2,4,5,9], where [9] provides full details of Leray's outline, while [2] extends (1.1) from the Lebesgue setting L p = L p,p to the general Lorentz setting L p,q . An altogether different proof of (1.1)p<∞ when n = 3 (under the assumption lim tրT u(t) L p (R 3 ) = ∞) is provided by Robinson and Sadowski [11]; their proof uses energy estimates, and is closely aligned with the spirit of this present paper.…”
Section: Introductionmentioning
confidence: 99%
“…We adopt the convention that F f (ξ) = R n e −iξ•x f (x) dx for f ∈ S. We recall that the Fourier transform of a compactly supported distribution is a smooth function 9. For example, if F u is locally integrable near ξ = 0, then u ∈ S ′ h .…”
mentioning
confidence: 99%
“…The fundamental mathematical theory of the Navier-Stokes equations goes back to the pioneering work of Leray (1934) (see Ożański & Pooley (2017) for a comprehensive review of this paper in more modern language), who used a Picard iteration scheme to prove existence and uniqueness of local-in-time strong solutions. Moreover, Leray (1934) and Hopf (1951) proved a global-in-time existence (without uniqueness) of weak solutions satisfying the energy inequality, u(t) 2 + 2ν t s ∇u(τ ) 2 dτ ≤ u(s) 2 (1.2) for almost every s ≥ 0 and every t > s (often called Leray-Hopf weak solutions) in the case of the whole space R 3 (Leray) as well as in the case of a bounded, smooth domain Ω ⊂ R 3 (Hopf).…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental mathematical theory of the Navier-Stokes equations goes back to the pioneering work of Leray (1934) (see Ożański & Pooley (2017) for a comprehensive review of this paper in more modern language), who used a Picard iteration scheme to prove existence and uniqueness of local-intime strong solutions. Moreover, Leray (1934) and Hopf (1951) proved the global-in-time existence (without uniqueness) of weak solutions satisfying the energy inequality,…”
Section: Introductionmentioning
confidence: 99%